KAJIAN MACAM PUPUK HAYATI TERHADAP INTENSITAS KERUSAKAN HAMA BELALANG PADA TANAMAN JAGUNG HITAM - Aulia Wahyu Dewantara; Dewi Ratna Nurhayati; Sartono Joko Santosa (Innofarm:Jurnal Inovasi Pertanian, 2020)
This study is entitled Study of Biofertilizer Types of Grasshopper Pest Intensity on Black Corn (Black Aztec) with the aim to study the types of biological fertilizer on grasshopper pest intensity. which began on November 9, 2019, in Jembangan Hamlet, Gagaksipat Village, Ngemplak District, Boyolali District, Central Java, with a height of 150m (asl). This research uses factorial basic design complete randomized block design (RCBD) arranged in a single factor consisting of 10 treatments 3 replications. From the results of this study were analyzed with the Dancun multiple range test (Duncan Multiple Range Test / DMRT) at a level of 5%. Observations observed included: symptoms of attack, intensity of attacks, fresh weight of cob with skin, fresh weight of stover, weight of 100 seeds. The results of the research show that: (1) Symptoms of locust pest attacks appear evenly on Biotogrow biofertilizers, symptoms of pest attacks begin to appear at the age of 20 days after planting. (2) The treatment of biological fertilizers affects the intensity of pest attacks on maize plants with the highest Biotogrow biofertilizers namely 22.6 and the lowest attacks on Megarizho fertilizers namely 13.8. (3) Megarizho biological fertilizer treatment can reduce locust pest attack,.